Pelaksanaan Fungsi Pengawasan Pada Kampanye Pemilihan Kepala Daerah - Ery Lilik Suryani Turnip; Caroline Paskarina; Firman Manan (Perspektif: Jurnal Ilmu-ilmu Sosial)
This paper examines the supervisory function of Election Supervisory Board (Bawaslu) in the 2018 West Kalimantan Governor and Vice Governor election, particularly in campaign administration. The campaign period in electoral cycle is one of the key stages in political contestation that it is vulnerable to malpractices, moreover it involves many parties and masses. The campaign malpractices that often occur are administrative irregularities, involvement of civil servants, and money politics. This paper employed a descriptive qualitative method by using data that were collected through interview and document study during the period October - December 2019. The results of this research revealed that in carrying out the supervisory function, the West Kalimantan Election Supervisory Board carried out malpractices prevention and enforcement which synergize with supervision of the district/city to sub-district/village levels. By emphasizing on the prevention function, the West Kalimantan Election Supervisory Board arranged supervisory design built upon potential vulnerability, which based on sub-stages and regions, conducted socialization intensively in the community, and coordinated with the stakeholders. Meanwhile, in the enforcement function, the West Kalimantan Election Supervisory Board cooperated with General Election Commissions (KPU), police and prosecutors.